Nature Based Solutions for Urban Resilience: A Distinction Between No-Tech, Low-Tech and High-Tech Solutions - Snep, Robbert PH; Voeten, Joris GWF; Mol, Gerben; Van Hattum, Tim (Frontiers in Environmental Science, 2020)
Urbanization and extreme weather require smarter urban water management. Nature-based solutions (NBS) like vegetated roofs and city trees can contribute effectively to climate resilience and future proof urban water management. However, large scale implementation is limited due to a lack of knowledge among professionals on how to capture, store and reuse water on-site. In this paper we advocate a classification into no-tech, low-tech and high-tech green, thereby supporting urban designers to better utilize the ability of these green elements to effectively manage water flows in different urban settings. Here, ‘no tech’ green is considered traditional urban green, handling (rain)water like nature would. ‘Low-tech’ green (e.g. extensive Sedum roofs) are suitable for dense urban settings with limited demand for water management and ecosystem services. More developed ‘high-tech’ green solutions have vegetation performing even beyond natural capacities, offering full water management control options and enable city planners, architects and landscape designers to enhance urban resilience and circularity without claiming valuable urban space. We elaborate our ‘tech NBS’ approach for city trees and vegetated roofs thereby demonstrating the classification’s added value for sustainable urban design. We conclude that specifying the demanded ‘no/low/high’ -tech level of green infrastructure in urban design plans will help to yield the most of ecosystem services using appropriate levels of available technology.